ST‐elevation myocardial infarction in a migrant population: a registry‐based study of patient treatment and outcomes. Issue 4 (7th April 2019) - Rye, Eleanor; Lee, Andrea; Mukhtar, Hadia; Narayan, Arun; Robert Denniss, A.; Chow, Clara; Kovoor, Pramesh; Sivagangabalan, Gopal
Abstract: Background: Internationally, a growing number of studies has identified race‐related disparities in the presentation, treatment and outcomes of patients with ST‐elevation myocardial infarction (STEMI). With a large migrant population, Australia presents a unique microcosm in which to study the impact of migrant status and ethnicity in STEMI patients. Aim: To investigate if first‐generation migrants differed in presentation, treatment or outcomes following STEMI compared with the Australian‐born population. Methods: We conducted a retrospective observational study using data from a clinician‐initiated registry. The study involved 2154 patients who presented to 12 hospitals between 2004 and 2012. Our main outcome measures included time to reperfusion, 30‐day mortality and complications. Results: Migrants ( n = 1035, 48.8%) were more likely to be older (61 vs 58 years, P < 0.001), diabetic (29.3 vs 21.5%, P < 0.001) and have a prolonged symptom to door time (102 vs 91 min, P = 0.04). Despite lower rates of previous known ischaemic heart disease (22.5 vs 26.6%, P = 0.03), migrants had more diffuse disease (triple vessel or left main (3VD/LM): 29.8 vs 22.0%, P < 0.001) and higher troponin values (3.77 vs 3.22 μg/L, P = 0.01). We found no significant differences in hospital treatment times, intervention types or rates. Multivariate regression identified age, diabetes, female gender and multi‐vessel disease as predictors of complications and death at 30 days. Conclusions: Migrants had longer pre‐hospital delays and exhibited different cardiovascular risk profiles than Australian‐born patients but received comparable treatment in the acute hospital setting. Higher rates of diabetes and multi‐vessel coronary artery disease were seen among migrant patients, indicating a relatively higher risk population.